EVALUASI IMPLEMENTASI PELAYANAN KEFARMASIAN PADA PUSKESMAS DI KABUPATEN PANDEGLANG TAHUN 2024 - Yusransyah, Yusransyah; Stiani, Sofi Nurmay; Nasiti, Febriane Dwi; Kelutur, Faruk Jayanto; Udin, Baha (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Pharmaceutical services are considered by some observers to be below standard. Both pharmacists and pharmaceutical technicians as health technicians are required to improve their skills, knowledge and behavior in order to provide quality direct services to patients. The purpose of this study was to determine the implementation of pharmaceutical services at Health Centers in Pandeglang Regency in 2023. This study is an observational study with a case study design. The method used is descriptive using checklist sheets and open statements. Based on the results of this study, there are significant differences in the aspects of facilities and infrastructure and clinical pharmacy services and there are differences but not significant in the aspects of managing pharmaceutical preparations and disposable medical materials. The conclusion of this study is that pharmaceutical services at Health Centers in Pandeglang Regency are in accordance with Permenkes No. 74 of 2016 by obtaining a percentage value of 79%, entering the GOOD category.